PRODUCTION OF MYCOBACTERIUM TUBERCULOSIS TB10.4 RECOMBINANT PROTEIN IN ESCHERICHIA COLI - I. V. Dukhovlinov (Sankt-Peterburg : NIIÈM imeni Pastera, 2016)
Nowadays tuberculosis is considered one of the most dangerous infectious diseases occurring everywhere, and it remains a cause of death of millions of people around the world. According to the World Health Organization data, in 2013 tuberculosis caused more than 9 million cases worldwide and about 1.5 million of infected people died. The causative agent of tuberculosis in most cases is Mycobacterium tuberculosis. But sometimes it can be Mycobacterium bovis or Mycobacterium africanum. Mainly as a result of infection, a bacterial infection affects the lungs, but the disease may develop in other organs and tissues. Now for the prevention of tuberculosis vaccination of newborns with attenuated vaccine BCG is widely used. The production of this vaccine is cheap and it is safe to use. Thus today, vaccination is the primary means of prevention of tuberculosis. However dubious efficacy and a number of side effects observed after vaccination, makes the scientific community to develop new effective methods for the treatment of tuberculosis. One of the ways to develop new vaccines against tuberculosis is to provide a subunit vaccine based on recombinant proteins. Advantages of subunit vaccines are that the preparation containing the purified protein is stable and secure, its chemical properties are known, it does not contain additional proteins and nucleic acids, which could cause undesirable effects in the human body. One of the most promising antigens for use as components in new vaccines is considered a low molecular weight secreted protein TB10.4. TB10.4 protein is recognized at an early stage of tuberculous infection and contributes to the proliferation of lymphocytes responsible for the production of IFNγ. TB10.4 protein also possesses an adjuvant effect when administered in combination with mycobacterial proteins. Given these properties, the recombinant protein TB10.4 can be used to generate new candidate vaccines against tuberculosis. During the study was created high-yield E. coli strain, which produces the recombinant protein TB10.4, selected the optimal protocol of induction of the gene encoding the protein. The protein was purified using metal affinity chromatography. The purity of the final preparation reached 98%.